2019
DOI: 10.1017/s0022029919000256
|View full text |Cite|
|
Sign up to set email alerts
|

Casein composition and differential translational efficiency of casein transcripts in donkey's milk

Abstract: The amount of the four caseins (αs1, αs2, β and κ-CN) in donkey milk was evaluated by Urea-PAGE analysis at pH 8.6, followed by immuno-detection with polyclonal antibodies, coupled to densitometric analysis. The results showed the percentage of each casein in decreasing order: β (54.28) > αs1 (35.59) > αs2 (7.19) > κ-CN (2.79). The mRNA quantification of donkey casein transcripts, carried out by RT-qPCR, showed that the average percentage of corresponding gene transcripts (CSN2, CSN1S1, CSN1S2 I and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In particular, Cn/Wp is less than one third with respect to cow milk; the casein micelle is larger and contains a different pattern of single fractions, with β-casein being the most abundant and k-casein present in trace amounts ( Table 1 ). However, recent research is supplying evidence of a wide genetic variability in synthetizing the αs1 fraction, suggesting that the casein pattern can present wide variations from individual to individual [ 20 , 21 , 22 ]. The scarce presence of k-casein is responsible of higher average size of the micelle and different mechanisms for micelle stability with respect to cow milk [ 23 , 24 , 25 ]; these characteristics, together with the low total casein content, are probably involved in the poor coagulation properties.…”
Section: Technological Properties Of Milkmentioning
confidence: 99%
“…In particular, Cn/Wp is less than one third with respect to cow milk; the casein micelle is larger and contains a different pattern of single fractions, with β-casein being the most abundant and k-casein present in trace amounts ( Table 1 ). However, recent research is supplying evidence of a wide genetic variability in synthetizing the αs1 fraction, suggesting that the casein pattern can present wide variations from individual to individual [ 20 , 21 , 22 ]. The scarce presence of k-casein is responsible of higher average size of the micelle and different mechanisms for micelle stability with respect to cow milk [ 23 , 24 , 25 ]; these characteristics, together with the low total casein content, are probably involved in the poor coagulation properties.…”
Section: Technological Properties Of Milkmentioning
confidence: 99%
“…The lower casein concentration in donkey's milk (about 50% of total protein) compared with bovine milk (80% of total protein) (Zicker and Lonnerdal 1994) and the relevant percentage of essential amino-acids make this milk a new dietetic food and a promising breast milk substitute (Guo et al 2007). A more recent study on donkey milk has revealed the percentage of four caseins (αs1, αs2, β and κ-CN) in decreasing order: β (54.28) > αs1 (35.59) > αs2 (7.19) > κ-CN (2.79) as evaluated by Urea-PAGE analysis at pH 8.6, followed by immuno-detection with polyclonal antibodies, coupled to densitometric analysis (Cosenza et al 2019).…”
Section: Milk Compositionmentioning
confidence: 99%